2015
DOI: 10.1021/cb5009734
|View full text |Cite
|
Sign up to set email alerts
|

A Genetically Encoded FRET Sensor for Intracellular Heme

Abstract: Heme plays pivotal roles in various cellular processes as well as in iron homeostasis in living systems. Here, we report a genetically encoded fluorescence resonance energy transfer (FRET) sensor for selective heme imaging by employing a pair of bacterial heme transfer chaperones as the sensory components. This heme-specific probe allows spatial-temporal visualization of intracellular heme distribution within living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 22 publications
3
93
3
1
Order By: Relevance
“…For instance, a reevaluation of the heme dissociation constants of the HRM-containing transcription factor Rev-erbβ found that heme binds 100-fold tighter than previously estimated, with K d III and K d II of ∼20 nM vs. 2-6 μM (20). Our observation that subcellular [LH] is heterogeneous stands in striking contrast to a recent report by He and coworkers (19) that used a heme chaperone-based FRET sensor (CISDY-9) for heme in human cell lines. In that work, cytosolic, mitochondrial, and nuclear heme were all reported to be ∼25 nM.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…For instance, a reevaluation of the heme dissociation constants of the HRM-containing transcription factor Rev-erbβ found that heme binds 100-fold tighter than previously estimated, with K d III and K d II of ∼20 nM vs. 2-6 μM (20). Our observation that subcellular [LH] is heterogeneous stands in striking contrast to a recent report by He and coworkers (19) that used a heme chaperone-based FRET sensor (CISDY-9) for heme in human cell lines. In that work, cytosolic, mitochondrial, and nuclear heme were all reported to be ∼25 nM.…”
Section: Discussioncontrasting
confidence: 95%
“…One variant, HS1-M7A, which was generated by replacing the heme axial Met 7 II value of HS1-M7A is similar in magnitude to previous estimates of the "regulatory" heme pool, 10-100 nM (12,19), as well as the affinities of proteins that may respond to this pool, including the heme-dependent transcription factor Rev-erbβ (20) and constitutive heme oxygenase-2 (HO-2) (21) (SI Appendix, Fig. S3G).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…20,21 Another strategy for heme imaging in live cells is based on the principle that association of heme either enhances or attenuates the fluorescence resonance energy transfer (FRET) process or quenches the fluorophore. 2225 Typically, these sensors recognize only labile heme. 22,23,25 Moreover, the FRET sensors could perturb normal heme homeostasis by sequestering heme and distorting labile heme.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dual-color photoswitchable fluorescent (DCPF) nanoparticles represent a new class of materials for exploitation of fluorescent technique in biological [1][2][3]. These fluorescent nanoparticles, based on fluorescence resonance energy transfer (FRET) phenomenon, have received many attentions because of some advantages over conventional fluorescent dyes as distinguishing fake positive signals by aberrant fluorescent biomolecules and targeted locations [4,5].…”
Section: Introductionmentioning
confidence: 99%